Analisis Neraca Air Pada Wilayah Sungai Barito - Miranti, Febry Asthia; Riduan, Rony (Lambung Mangkurat University Press, 2024)
The study of water balance is an analysis of the equilibrium between water demand (demand system) and water availability (supply system). Current conditions show that the water balance tends to become increasingly critical, leading to conflicts of interest in water use. Therefore, optimizing water allocation in a watershed (DAS) is necessary by considering water users and the regulations applicable within the administrative area where the watershed is located. The location of the water balance analysis research is in the Barito River Basin, which consists of the Barito Watershed, Kapuas Watershed, Maluka Watershed, and Tabanio Watershed. In this study, the Barito Watershed is the largest watershed within the Barito River Basin, crossing two provinces, namely Central Kalimantan Province and South Kalimantan Province. The aim of this research is to provide water balance calculations that can serve as a basis for developing water allocation concepts in the form of an annual water supply plan. The data used in the water balance analysis include spatial data, hydrological data, and walkthrough implementation data. The results of the water allocation modeling provide an overview of the extent to which water demand is met under existing conditions and can serve as a consideration if there is an increase in water utilization rates for each user in the future.